Acute Phase Proteins in Marine Mammals: State of Art, Perspectives and Challenges - Gelain, Maria Elena; Bonsembiante, Federico (Frontiers in Immunology, 2019)
The term ‘acute phase response’ (APR) is referred to a nonspecific and complex reaction of an organism that occurs shortly after any tissue damage, such as infection, trauma, neoplasia, inflammation, and stress. The APR can be identified and monitored with some laboratory tests, such as the concentration of several plasma proteins, the acute phase proteins (APPs). The APPs are components of the non-specific innate immune response, and their plasma concentration is proportional to the severity and/or the extent of tissue damage. The evaluation of health status of marine mammals is difficult because the classical clinical signs of illness used for human and domestic animals are difficult to recognize and understand. For this reason, in the past years, several efforts were done to identify laboratory markers of disease in these animals. The APPs have demonstrated their role as early markers of inflammation in veterinary medicine, thus several APPs were tested in marine mammals, such as C-reactive protein (CRP), serum amyloid-A (SAA), and Haptoglobin (Hp). However, the difficulty to extrapolate the knowledge about APPs in one species to another, the lack of specie-specific reagents, the absence of data about negative APPs have hampered their extent use in marine mammals. Herein, the state of art of APPs in marine mammals is reviewed, with particular attention to pre-analytical and analytical factors that should be taken into account in validation and interpretation of APPs assays. Moreover, the current application, potential utility and the future developments of APPs in marine mammals is highlighted and discussed.